Noma finally recognised as a neglected tropical disease. - Stuart Ainsworth (Public Library of Science (PLoS), 2024)
In December 2023, after decades of tireless advocacy from stakeholders and partners, the World Health Organization (WHO) gave noma the long overdue recognition as a neglected tropical disease. The significance of this official recognition cannot be overstated, and it is hoped this will serve as a turning point in our battle against this devastating disease.